2008
DOI: 10.1093/brain/awp024
|View full text |Cite
|
Sign up to set email alerts
|

Dual mechanism of brain injury and novel treatment strategy in maple syrup urine disease

Abstract: Maple syrup urine disease (MSUD) is an inherited disorder of branched-chain amino acid metabolism presenting with life-threatening cerebral oedema and dysmyelination in affected individuals. Treatment requires life-long dietary restriction and monitoring of branched-chain amino acids to avoid brain injury. Despite careful management, children commonly suffer metabolic decompensation in the context of catabolic stress associated with non-specific illness. The mechanisms underlying this decompensation and brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
129
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(144 citation statements)
references
References 38 publications
12
129
1
2
Order By: Relevance
“…Additionally, Linck and colleagues (2012) have demonstrated that AMPA receptors play a key role in the mechanism of the antidepressant-like action of NAC by indirectly modulating the serotonin and noradrenaline pathways. Consistent with these mechanisms, reduced cerebral dopamine and glutamate levels have been observed in experimental MSUD animals (Dodd et al 1992;Zinnanti et al 2009) and postmortem brain tissue from a child who died of leucine intoxication (Prensky and Moser 1996).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Additionally, Linck and colleagues (2012) have demonstrated that AMPA receptors play a key role in the mechanism of the antidepressant-like action of NAC by indirectly modulating the serotonin and noradrenaline pathways. Consistent with these mechanisms, reduced cerebral dopamine and glutamate levels have been observed in experimental MSUD animals (Dodd et al 1992;Zinnanti et al 2009) and postmortem brain tissue from a child who died of leucine intoxication (Prensky and Moser 1996).…”
Section: Discussionmentioning
confidence: 75%
“…The worldwide frequency is approximately 1:185,000 based on routine screening data from 26.8 million newborns (Chuang and Shih 2001). Individuals with MSUD usually present with poor feeding, convulsions, ketoacidosis, hypoglycemia, coma, ataxia, psychomotor delay, and mental retardation, as well as generalized edema and hypomyelination/ demyelination shown by magnetic resonance imaging studies of the central nervous system (Chuang and Shih 2001;Cavalleri et al 2002;Ha et al 2004;Sch€ onberger et al 2004;Zinnanti et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…10 Foi demonstrado que a rápida acumulação cerebral de leucina desloca outros aminoácidos essenciais, conduzindo à depleção de neurotransmissores e à interrupção do crescimento e desenvolvimento normal do cérebro. 10 Os valores normais de leucina sérica variam entre 80 e 200 µmol/L. 7 Valores de leucina superiores a 1000 µmol/L de forma sistemática relacionam-se com desenvolvimento intelectual negativo.…”
Section: Discussionunclassified
“…With respect to the latter, mouse model experiments have shown lower CSF levels of glutamate, dopamine, and GABA, as well as lower plasma levels of tryptophan, the precursor to serotonin (Zinnanti et al 2009). The BCKAs appear to exert effects, at least partially through disruption of pyruvate metabolism (Patel et al 1973) and respiratory chain function (Sgaravatti et al 2003).…”
Section: Discussionmentioning
confidence: 99%